Kinetic and thermodynamic studies of polyvinyl chloride composite of manganese oxide nanosheets for the efficient removal of dye from water - Tooba Saeed (IWA Publishing, 2021)
Manganese oxide nanosheets and manganese oxide composite with polyvinyl chloride (MnO2-PVC) were synthesized by the oxidation method for the efficient removal of Congo red (CR). The Fourier transform infrared spectroscopy, X-ray diffraction, energy dispersive X-ray, surface area (SA), point of zero charge (PZC) and thermogravimetric analysis were performed to verify the newly synthesized adsorbents. After functionalizing the surface of MnO2 nanosheets with PVC, the PZC and SA were amplified from 4.10 and 214 m2g−1 to 5.01 and 226 m2g−1, respectively. The batch adsorption results showed that the removal capacity of CR on both the adsorbents decreased with the increase of pH and time, but increased with the increase of adsorbent dosage. However, due to the high stability, porosity and greater surface area, the PVC composite of MnO2 was found to exhibit 15 times greater CR removal efficiency than its parent MnO2. Furthermore, the thermodynamic parameters specified that CR adsorption onto both the adsorbents was exothermic, spontaneous and film diffusion accompanied by the intraparticle diffusion is the rate controlling step. These results validate that MnO2 composite with PVC is a useful, eco-friendly, competent candidate for dye removal from wastewater. HIGHLIGHTS The current study is competent and environmentally benign for the removal of anionic dye from model aqueous solution.; The high adsorption capacity of the composite material credited to its unique properties of such as high surface area and porosity.; The rate controlling step depends on the intra-particle diffusion as well as film diffusion.;